2004
DOI: 10.1530/rep.1.00057
|View full text |Cite
|
Sign up to set email alerts
|

Staging of ovine embryos and expression of the T-box genes Brachyury and Eomesodermin around gastrulation

Abstract: The high rates of embryonic mortalities which follow in vitro production of ruminant embryos have emphasized the need for increased knowledge of early development. It is likely that early failures in embryonic development and placenta formation involve abnormal differentiation of mesoderm. The aim of this study was to investigate the pattern of expression of two T-box genes known to control the gastrulation process, Brachyury and Eomesodermin, by whole-mount in situ hybridization. To allow a more precise compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
6
38
0
Order By: Relevance
“…The lack of pluripotency in the pig ICM may explain the diffi culty in establishing ESC from blastocysts. Previous reports have demonstrated that pig ICM derived from Day 8 blastocysts transit to an epiblast phenotype after 2-3 days in culture [ 34 ] and they rapidly differentiate [ 27 ]. Here, we cultured isolated epiblasts using conditions that support hESC and mEpiSC growth.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The lack of pluripotency in the pig ICM may explain the diffi culty in establishing ESC from blastocysts. Previous reports have demonstrated that pig ICM derived from Day 8 blastocysts transit to an epiblast phenotype after 2-3 days in culture [ 34 ] and they rapidly differentiate [ 27 ]. Here, we cultured isolated epiblasts using conditions that support hESC and mEpiSC growth.…”
Section: Discussionmentioning
confidence: 98%
“…The epiblast at this stage of development transitions from a round oblong disc to a developmentally advanced pear-shaped embryonic disc with a narrow posterior end [ 26 ]. Early round oblong epiblasts identifi ed under a stereomicroscope can be easily separated from the remaining trophoblast cells on the basis of their contrasting appearance [ 27 ]. The underlying PE cells, which are transparent cells and have a globular phenotype, can be distinguished from the epithelial cells of the epiblast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion of the trophoblast provides an increased placental surface area to enable maternal:conceptus cross-talk and nutrient exchange that are essential for the survival of the conceptus (Stroband & Van der Lende 1990). Accompanying elongation is the degradation of the sheath of trophoblasts cells covering the embryonic disc (Rauber's layer) exposing the cells of the embryonic disc to the maternal milieu (Marrable 1971, Guillomot et al 2004). In the ewe and cow blastocyst, trophoblast elongation is initiated around gestational day 11 (gd11) and gd12 respectively, and transition from the ovoid to filamentous stage is complete after several days (ewe, gd16;cow, gd18;Bazer et al 1993, Guillomot et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying elongation is the degradation of the sheath of trophoblasts cells covering the embryonic disc (Rauber's layer) exposing the cells of the embryonic disc to the maternal milieu (Marrable 1971, Guillomot et al 2004). In the ewe and cow blastocyst, trophoblast elongation is initiated around gestational day 11 (gd11) and gd12 respectively, and transition from the ovoid to filamentous stage is complete after several days (ewe, gd16;cow, gd18;Bazer et al 1993, Guillomot et al 2004. In cattle, trophoblast cells start to elongate at gd14 and the embryonic membrane can extend the entire length of both uterine horns by gd24.…”
Section: Introductionmentioning
confidence: 99%